The European Prevention of Alzheimer's Dementia Programme: An Innovative Medicines Initiative-funded partnership to facilitate secondary prevention of Alzheimer's disease dementia - Saunders, Stina; Gregory, Sarah; Clement, Matthew H. S.; Birck, Cindy; Geyten, Serge van der; Ritchie, Craig W. (Frontiers in Neurology, 2022)
Introduction: Tens of millions of people worldwide will develop Alzheimer’s disease (AD). Collectively utilising data, samples and knowledge amassed by large-scale projects like the Innovative Medicines Initiative (IMI) funded European Prevention of Alzheimer’s Dementia (EPAD) program will enable the research community to learn, adapt, and implement change. Method: In the current paper, we define and discuss the substantial assets of the EPAD project for the scientific community, patient population and industry, describe the EPAD structure with a focus on how the public and private sector interacted and collaborated within the project, reflect how IMI specifically supported the achievements of the above, and conclude with a view to the future. Results: The EPAD project was a €64 million investment to facilitate secondary prevention of AD dementia research. The project recruited over 2,000 research participants into the EPAD longitudinal cohort study (LCS) and included over 400 researchers from 39 partners. The EPAD LCS data and biobank are freely available and easily accessible via Alzheimer's Disease Data Initiative’s (ADDI) AD Workbench platform and University of Edinburgh’s Sample Access Committee. Discussion: Through GAP, IMI-Neuronet and follow-on funding from the Alzheimer’s Association for the data and sample access systems, the EPAD assets will be maintained and, as and when sponsors seek a new platform trial to be established, the learnings from EPAD will ensure that this can be developed to be even more successful than this first pan-European attempt.